Financial Inclusion: A review of Mobile Money Interoperability in Zimbabwe - Maune, Alexander; Nyakwawa, Gerald M.; Magara, Tinashe (Acta Universitatis Danubius. Œconomica, 2022)
Objectives: This article examined whether moral suasion from the national payments system directorate works in Zimbabwe. Moreover, the study examined whether the country needs arbitration for mobile money interoperability or is now at a point where there is a need for mandatory regulatory intervention. Prior work: This article builds on the acceptance and use of mobile phones as a powerful financial inclusion tool used by telecommunication and banking institutions as they scramble for market share for their mobile financial products and services. Approach: A qualitative approach underpinned by a review of related literature and relevant documents guided the study. Results: Despite the availability and existence of mobile money wallets since 2011, nothing has taken place regarding interoperability as an option in Zimbabwe. The financial inclusion strategy had provided guidelines towards mobile money interoperability. Implications: The study has policy implications on issues surrounding regulatory interventions. The article closes the knowledge gap in mobile money interoperability in Zimbabwe. Value: The study is unique and critical in providing an overview of the subject matter from a qualitative point of view.